Development and perfection of the enterprise information system of wholesale-retail trade - Загоровська, Лариса Григорівна; Ковтун, Олександр Михайлович (Eastern-European Journal of Enterprise Technologies, 2012)
The question of development and improvement of the information system of enterprise of wholesale-retail trade is considered. The model of biznes-process of enterprise is developed, the structure of database is improved and functionality of the system is extended by integration and adaptation of developed SCM-mogul.